Effects of clomiphene citrate and anastrozole as a combination therapy for hypogonadism: A systematic review and meta-analysis - Padmashobana Bagavathithasan; Swati Sucharita Dash; Lakshmi Venkatachalam; Vaishali Amol Shetye; Shashwati Pankaj; Jignesh Bhate; Guruprasad K S Rao (Annals of Medical Science and Research)
Clomiphene citrate (CC) and anastrozole (AZ) combination has been used off-label to improve spermatogenesis in male infertility. This systematic literature review and meta-analysis evaluated the efficacy and safety of CC and AZ combination therapy in subfertile hypogonadal men. Studies were systematically searched and retrieved from PubMed, Web of Science, CENTRAL, and ClinicalTrials.gov from inception to May 19, 2021, using MeSH terms/keywords. Statistical analysis was performed using a random effects model, pooled risk ratio, and heterogeneity (I2). The methodological quality of the studies was assessed utilizing the Newcastle–Ottawa Scale and Moga tools. Overall, 37 studies were identified from a systematic search, and two studies that met the eligibility criteria were considered for quantitative synthesis. Treatment with combination therapy (CC + AZ) and monotherapy (CC) significantly increased the total testosterone (TT), bioavailable testosterone (BT), estradiol level, and testosterone/estradiol (T/E) ratio from baseline (P < 0.00001). In comparison with monotherapy, combination therapy increased TT (mean difference [MD]: 56.29; 95% confidence interval [CI], 12.36, 100.22; P = 0.01) and BT (MD: 48.18; 95% CI, 8.19, 88.17; P = 0.02) levels in blood. Monotherapy elevated the estradiol level and decreased T/E ratio, whereas combination therapy reduced the estradiol (MD: -2.17; 95% CI, -59.89, 55.55; P = 0.94) level and optimized T/E ratio (MD: 3.64; 95% CI, -18.90, 26.18; P = 0.75). P-specific antigen and hematocrit levels were measured to evaluate the safety of combination and monotherapy. Combination therapy with CC and AZ was safe and well-tolerated in hypogonadal men.